PENATAAN TAMAN DALAM KAJIAN BALI SEBAGAI PULAU TAMAN YANG BERBUDAYA - Darma, I Dewa Putu (Bumi Lestari; Vol 5 No 1, 2012)
Bali is one of famous tourism object in the world. To realize Bali as a park island ofculture, it is necessary to be attention in improvement Bali itself. Between human being andnature are interlocked to make Bali as a park island. In fact at the field that the arrangementof park in Bali has not reflected life culture of Balinese people, where the used of plants hasnot referenced for the kinds of the plats which is used to religion ceremony, holy building,medicines an so on, According to the result of the research the selection of the kinds of theplants is used to arrange the park in Bali, have inventarization as 105 kinds. To realize Balias park island of culture so government, private and people to needed.
Keywords: park, Bali and culture.